Genetic Parameters of Embryonic Viability Traits in a Traditional Chicken Breed - Lariviere, J.-M.; Michaux, C.; Leroy, P. (International Journal of Poultry Science, 2009)
The common practice of candling chicken eggs during incubation, allows classification of embryonic mortality at three stages: early, mid-term and late embryonic development. The purpose of this study was to estimate genetic parameters of embryonic mortality at three stages of incubation as well as fertility and hatchability in an ancient chicken breed. Hatchability of fertile eggs had a favourable genetic correlation with early (-0.09) and mid-term (-0.36) embryonic mortality. Hatchability of eggs set was favourably correlated with mid-term embryonic mortality (-0.40) but not with early (0.22) embryonic mortality. Genetic correlations between fertility and hatchability of fertile eggs and hatchability of eggs set were 0.20 and 0.86, respectively. Genetic correlations between late and early embryonic mortality (0.11) and mid-term embryonic mortality (0.34) were favourable, but not between early and mid-term (-0.78) embryonic mortality. Mid-term embryonic mortality and hatchability of fertile eggs were both candidate traits for effective selection against embryonic mortality in our breed. Benefits are brought by the high heritability value of mid-term embryonic mortality and its advantageous correlation with fertility, late embryonic mortality, hatchability of fertile eggs and hatchability of eggs set. On the other hand, it is more convenient to measure hatchability of fertile eggs, which also has a favourable correlation with fertility, early and mid-term embryonic mortality.